Application of Strobilurins and Carboxamides Improves the Physiology and Productivity of Tomato Plants in a Protected Environment - Jacobelis, Walter [UNESP]; Aires, Eduardo Santana [UNESP]; Ferraz, Andrew Kim Lopes [UNESP]; Marques, Isabelly Cristina da Silva [UNESP]; Freitas, Francisco Gilvan Borges Ferreira [UNESP]; Silva, Dayane Mércia Ribeiro [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (MDPI, 2023)
The use of fungicides from the strobilurin and carboxamide groups demonstrates an effect on photosynthetic efficiency by increasing CO2 assimilation and, consequently, plant productivity, due to better a physiological performance. The objective was to evaluate the effect of the application of these fungicides on the physiology and yield of tomato plants. A randomized block design was used with six treatments and five blocks: control, azoxystrobin (75 g ha−1), boscalid (75 g ha−1), pyraclostrobin (75 g ha−1), fluxapyroxad (75 g ha−1) and fluxapyroxad + pyraclostrobin (50.1 g and 99.9 g ha−1). Different physiological, biochemical and antioxidant enzymatic parameters were evaluated. The application of fungicides increased the CO2 assimilation by 64% and the production per plant by 91%. The activity of the nitrate reductase enzyme increased by 1.69 times, the antioxidant system by 3.68 times and photosynthetic pigments by 1.16 times under the action of the studied fungicides with respect to the control. Therefore, the application of fungicides favored the development of the tomato plant, especially with the use of Pyraclostrobin (75 g ha−1).
Keywords: antioxidant enzymes; fungicide; gas exchange; Solanum lycopersicumL; yield